2022
DOI: 10.1097/aog.0000000000004686
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-Care Viscoelastic Tests in the Management of Obstetric Hemorrhage

Abstract: Obstetric hemorrhage remains the leading cause of maternal morbidity and mortality worldwide. Thromboelastography and rotational thromboelastometry are laboratory methods of assessing the kinetics of blood clot formation through real-time measurement of viscoelastic clot strength and may aid in management of severe hemorrhage. Although first described more than 70 years ago, viscoelastic testing devices are now available that allow for rapid point-of-care use of this technology to aid in real-time management o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 37 publications
0
5
0
1
Order By: Relevance
“…The authors of a recent clinical expert series in obstetrics and gynecology identified the utility of POC testing with TEG in PPH but noted that published data in the obstetrics literature were lacking. 17 Our study adds to the growing body of evidence to support the use of TEG for targeted resuscitation in ongoing PPH.…”
Section: Discussionmentioning
confidence: 70%
“…The authors of a recent clinical expert series in obstetrics and gynecology identified the utility of POC testing with TEG in PPH but noted that published data in the obstetrics literature were lacking. 17 Our study adds to the growing body of evidence to support the use of TEG for targeted resuscitation in ongoing PPH.…”
Section: Discussionmentioning
confidence: 70%
“…Gemelli's pregnancy is thought to be able to trigger severe preeclampsia because it causes hyperplacentosis. Hyperplacentosis is believed to increase antiangiogenic levels circulating in the maternal circulation, affecting the balance of angiogenic and antiangiogenic factors (Nelson, Ogunkua, & Cunningham, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…In recent years there has been increasing use of point-of-care viscoelastic haemostatic assay-guided blood product transfusion [ 48 ]. In an evaluation of a national quality improvement project in Wales including this technology, there were no deaths from haemorrhage among 60,914 maternities [ 49 ].…”
Section: Point-of-care Viscoelastic Haemostatic Assay-guided Blood Pr...mentioning
confidence: 99%